A STUDY ON MORAL REASONING AND ACADEMIC ACHIEVEMENT OF SECONDARY SCHOOL STUDENTS IN SATHYAMANGALAM TALUK OF ERODE DISTRICT - et. al., Father Sri Marshal Joseph, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Moral reasoning is mainly focusing on making right decisions to do right activities and exhibit good behaviour of school students in a particular situation and it provides chances for them to discover and realize values, to build character and to improve personality. The findings reveal that there exits significant difference amongst moral reasoning of secondary school students and their profile. Moral reasoning is positively and moderately related with academic achievement of secondary school students. Hence, secondary school teachers should give proper guidance to their secondary school students for improving their moral reasoning and ethical and moral behaviours. Parents must provide conducive home environment for their secondary school students to enhance their abilities for moral reasoning and academic achievement. Furthermore, secondary school teachers should interact, discuss and exchange ideas regularly with their secondary school students for increasing their moral reasoning and academic achievement. Peer groups and family members must also give moral support to their secondary school students for improving their moral reasoning and academic achievement. In addition, secondary schools should conduct various programmes for enhancing moral reasoning and academic achievement among their secondary school students.